2011
DOI: 10.1016/j.ejpb.2011.01.007
|View full text |Cite
|
Sign up to set email alerts
|

State of the art of nanocrystals – Special features, production, nanotoxicology aspects and intracellular delivery

Abstract: Drug nanocrystals are the latest, broadly introduced nanoparticulate carrier to the pharmaceutical market from the year 2000 onwards. The special features of nanocrystals for the delivery of poorly soluble drugs are briefly reviewed (saturation solubility, dissolution velocity, adhesiveness). The industrially relevant bottom up (precipitation) and top down production technologies (pearl milling, high pressure homogenization, combination technologies) are presented. As nanotoxicological aspects, the effect of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
309
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(339 citation statements)
references
References 43 publications
1
309
0
8
Order By: Relevance
“…Müller et al suggested a nanotoxicological classification system considering both particle size and biodegradability as important factors for nanotoxicity. 41 Thus, loading of the lysosomes with the non-degrading PS-COOH NPs appears to lead to some stress for the cells and to the observed increase in signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Müller et al suggested a nanotoxicological classification system considering both particle size and biodegradability as important factors for nanotoxicity. 41 Thus, loading of the lysosomes with the non-degrading PS-COOH NPs appears to lead to some stress for the cells and to the observed increase in signalling.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this objective, the particle size of coarse GLB was reduced by precipitation and the surface properties were improved by complexation. Complexation or coating could provide a higher circulation of NCs in blood, avoid clearance and facilitate higher cellular uptake of drug (Müller et al, 2011;Gao et al, 2012). This leads to the enhanced therapeutic effect and the drug can be targeted to the site.…”
Section: Discussionmentioning
confidence: 99%
“…This unusual result indicates that particle size and uniformity is crucial in NCs, because uneven NCs were not only invalid but also showed increased individual differences. Also, particles of size 155 nm are taken up by all cells by endocytosis and they are considered as high risk particles thereby decreasing the concentration of drug in site (Müller et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A large variety of drug delivery systems are described in the literature, such as liposomes (Torchilin, 2006), micro and nanoparticles (Kumar, 2000), polymeric micelles (Torchilin, 2006), nanocrystals (Muller et al, 2011), among others. Microparticles are usually classified as microcapsules or microspheres (Figure 8).…”
Section: Xylan Microparticlesmentioning
confidence: 99%